Method for preparing nano vaterite calcium carbonate from carbonized carbide slag
By using ammonium chloride as a leaching agent in the process of preparing vaterite calcium carbonate in the calcium carbide slag and combining with supergravity carbonization, the problems of large particle size distribution, low production efficiency and additives in the existing process are solved, and the effect of efficient preparation of nanovaterite calcium carbonate is achieved.
Patent Information
- Application Number
- CN202411806590.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
In the existing process of preparing vaterite calcium carbonate, the product has a large particle size distribution, low production efficiency and requires additives.
Ammonium chloride is used as leaching agent and the calcium carbide slag and stirred at room temperature. Then, the calcium-containing filtrate is passed into the outer circulating supergravity reactor and reacted with CO2 gas. Nanovaterite calcium carbonate is prepared by supergravity carbonization method.
实现了粒度小且分布均匀的纳米球霰石型碳酸钙的高效制备,降低了成本,提高了生产效率,无需添加剂,并实现了部分材料的循环利用。
Smart Images

Figure CN119612568A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization, and in particular relates to a method for preparing nano-vaterite calcium carbonate by carbonizing carbide slag. Background Art
[0002] Calcium carbide slag is a waste slag with Ca(OH)2 as the main component produced by industrial use of calcium carbide hydrolysis to obtain acetylene gas. Its output is huge, and the problems of large-scale accumulation and transportation difficulties are becoming increasingly serious. It is urgent to explore ways to use calcium carbide slag nearby and make it a treasure from waste. The recycling of calcium carbide slag in my country includes the production of cement, quicklime, chemical products and building materials. Calcium carbide slag is rich in calcium resources. Through mineralization with CO2, it can not only produce high-value-added calcium carbonate products and generate certain economic benefits, but also the stable carbonate formed can achieve permanent fixation of CO2, effectively reducing carbon emissions and alleviating global warming.
[0003] Nano calcium carbonate has anhydrous crystal structures of three different morphologies: calcite (trigonal rhombus), aragonite (orthorhombic needle-shaped) and vaterite (hexagonal spherical), with a particle size between 10-100nm, of which vaterite is second only to aragonite in stability. Nano vaterite calcium carbonate has the characteristics of low specific gravity, high luminescence, high refractive index, good suspension characteristics, etc., and is widely used in the fields of plastics, rubber, paper, coatings, paints, adhesives and inks. Adding it to products can increase volume, improve the flexural strength and elastic modulus thermal deformation temperature of products, and adding it to inks can improve its glossiness and stability. Therefore, preparing nano vaterite calcium carbonate using industrial solid waste carbide slag can not only reduce costs, save energy, but also protect the environment and promote the sustainable development of human society.
[0004] The preparation methods of nano vaterite calcium carbonate mainly include calcination digestion-carbonation method and calcium component leaching-carbonation method. Calcination digestion-carbonation method: carbide slag is mixed with ammonium sulfate and roasted at high temperature, and the roasted product is made into a suspension liquid, into which CO2 gas is passed or carbonates and bicarbonates are added, and nano vaterite calcium carbonate is directly carbonized in a carbonization reactor, but the roasting and calcining energy consumption is high, and the investment and operation cost is high. Calcium component leaching-carbonation method: inorganic ammonium salt is used to leach the calcium component in carbide slag, effectively separate impurities, and then CO2 gas is passed into the separated calcium-containing material or carbonates and bicarbonates are added, and nano vaterite calcium carbonate is carbonized in a carbonization reactor, which is low in cost and more environmentally friendly.
[0005] The Chinese patent with the publication number CN110040757A discloses a method for preparing light calcium carbonate using carbide slag, wherein the carbide slag is purified to remove impurities and other harmful substances, and the gas CO2 captured by industrial carbon is coupled to the carbide slag suspension for mixed reaction to prepare bead-shaped amorphous fine particles of light calcium carbonate. The Chinese patent with the publication number CN113620331B discloses a method for preparing nano-vaterite calcium carbonate from CO2-mineralized carbide slag, and introduces the use of ammonium sulfate as a carbide slag leaching agent through a step-by-step mild mineralization coupled flotation impurity removal process, and the addition of a dispersant for regulation to obtain nano-vaterite calcium carbonate.
[0006] Chinese patent publication number CN102602973A discloses a method for synthesizing ultrafine calcium carbonate using carbide slag, which introduces the use of ammonium chloride to effectively leach the active calcium component in the carbide slag, and the introduction of CO2 gas into the leaching solution to prepare ultrafine calcium carbonate.
[0007] Chinese patent publication number CN103738997A discloses a method for preparing nano calcium carbonate using carbide slag as raw material, introducing ammonium chloride as a leaching agent, introducing CO2 gas into the leaching solution and stirring to obtain calcium carbonate powder below 1000 mesh.
[0008] However, the calcium carbonate prepared by the carbide slag CO2 direct mineralization method reported in the above patent application has a large particle size distribution and incomplete impurity separation. The calcium carbonate obtained by the carbide slag indirect carbonation method has an uneven particle size distribution and requires the addition of additives, which is poor in economic efficiency. Summary of the invention
[0009] The technical problem to be solved by the present invention is to provide a method for preparing nano-vaterite calcium carbonate from carbide slag; the method aims to solve the problems of large product particle size distribution, low production efficiency and need for additives in the existing process for preparing vaterite calcium carbonate from carbide slag, and can efficiently prepare nano-vaterite calcium carbonate with small particle size (50-80nm) and uniform distribution.
[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0011] A method for preparing nano-vaterite calcium carbonate by carbonizing carbide slag comprises the following steps:
[0012] 1) Raw material pretreatment: dry the carbide slag and grind it into powder for later use;
[0013] 2) Leaching: Mix carbide slag, ammonium chloride and deionized water, stir at room temperature, and filter after reaction to obtain filter residue and calcium-containing filtrate;
[0014] 3) Carbonization reaction: The calcium-containing filtrate obtained in step 2) is introduced into an external circulation high gravity reactor (abbreviated as: RPB), and CO2 gas is introduced at the same time, carbonized at room temperature, and nano-vaterite calcium carbonate is obtained by filtering, washing and drying.
[0015] Preferably, in step 1), the drying temperature is 100-110° C., and the drying time is 3-12 h.
[0016] Preferably, in step 2), the weight ratio of carbide slag: ammonium chloride: deionized water is (3.3-5): (5.5-6.5): (32-37).
[0017] Preferably, in step 2), the concentration of the ammonium chloride solution after mixing is 3.0-4.5 mol / L.
[0018] Preferably, in step 2), the stirring speed is 800-900 r / min.
[0019] Preferably, in step 2), the stirring time is 40-70 min.
[0020] Preferably, in step 3), the flow rate of CO2 is 30-80 ml / min.
[0021] Preferably, in step 3), the rotor speed in the external circulation high gravity reactor is 2000-2850 r / min.
[0022] Preferably, in step 3), the circulation flow rate of the reaction liquid in the external circulation supergravity reactor is 40-60 L / h.
[0023] Preferably, in step 3), the circulation time of the reaction liquid in the external circulation supergravity reactor is 20-60 min.
[0024] Preferably, in step 3), the washing is performed with deionized water, and the number of washing times is 3-6 times.
[0025] Preferably, in step 3), the drying is oven drying at a temperature of 100-110° C. for a time of 3-12 h.
[0026] Preferably, in step 3), the dried solid phase is ground to obtain nano-vaterite calcium carbonate with an average particle size of 50 to 80 nm.
[0027] Preferably, in step 3), the filtrate after filtration is recovered and its concentration is adjusted to be used as a circulating leaching agent to react with carbide slag.
[0028] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0029] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) Carbide slag is an industrial solid waste rich in calcium components. The calcium ions therein can be extracted using ammonium chloride as a leaching agent to obtain a leaching rate of not less than 84%, and the obtained calcium-containing filtrate is used for subsequent carbonization reaction;
[0032] (2) Using carbide slag as raw material and adopting supergravity carbonization method, nano-vaterite calcium carbonate with small particle size and uniform distribution can be obtained, and the recovered ammonium chloride can be circulated to leach the carbide slag by adjusting the concentration;
[0033] (3) The process is simple, low cost, high production efficiency, no additive pollution, most of it can be recycled, and while comprehensively treating carbide slag, it can also achieve a certain degree of carbon emission reduction, which is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0035] Figure 1 The present invention is a schematic diagram of the whole process of preparing nano-vaterite calcium carbonate by carbonizing carbide slag using a supergravity reactor. DETAILED DESCRIPTION
[0036] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0037] As another aspect of the present invention, a method for preparing nano-vaterite calcium carbonate from carbonized carbide slag of the present invention comprises the following steps:
[0038] 1) Raw material pretreatment: dry the carbide slag and grind it into powder for later use;
[0039] 2) Leaching: Mix carbide slag, ammonium chloride and deionized water, stir at room temperature, and filter after reaction to obtain filter residue and calcium-containing filtrate;
[0040] 3) Carbonization reaction: The calcium-containing filtrate obtained in step 2) is introduced into an external circulation high gravity reactor (abbreviated as: RPB), and CO2 gas is introduced at the same time, carbonized at room temperature, and nano-vaterite calcium carbonate is obtained by filtering, washing and drying.
[0041] According to some embodiments of the present invention, in step 1), the drying temperature is 100-110° C., and the drying time is 3-12 hours.
[0042] According to certain embodiments of the present invention, in step 2), the weight ratio of carbide slag: ammonium chloride: deionized water is (3.3-5): (5.5-6.5): (32-37).
[0043] According to certain embodiments of the present invention, in step 2), the concentration of the ammonium chloride solution after mixing is 3.0-4.5 mol / L.
[0044] According to some embodiments of the present invention, in step 2), the stirring speed is 800-900 r / min.
[0045] According to certain embodiments of the present invention, in step 2), the stirring time is 40-70 min.
[0046] According to some embodiments of the present invention, in step 3), the flow rate of CO2 is 30-80 ml / min.
[0047] According to certain embodiments of the present invention, in step 3), the rotor speed in the external circulation high gravity reactor is 2000-2850 r / min.
[0048] According to certain embodiments of the present invention, in step 3), the circulation flow rate of the reaction liquid in the external circulation supergravity reactor is 40-60 L / h.
[0049] According to certain embodiments of the present invention, in step 3), the circulation time of the reaction liquid in the external circulation high gravity reactor is 20-60 min.
[0050] Preferably, in step 3), the washing is performed with deionized water, and the number of washing times is 3-6 times.
[0051] According to some embodiments of the present invention, in step 3), the drying is oven drying at a temperature of 100-110° C. for a time of 3-12 h.
[0052] According to certain embodiments of the present invention, in step 3), the dried solid phase is ground to obtain nano-vaterite calcium carbonate with an average particle size of 50 to 80 nm.
[0053] According to certain embodiments of the present invention, in step 3), the filtrate after filtration is recovered and its concentration is adjusted to be used as a circulating leaching agent to react with carbide slag.
[0054] The supergravity device used in the present invention is a prior art, such as the supergravity device disclosed in CN107684880A, such as the supergravity device disclosed in CN118204047A.
[0055] Example 1
[0056] A method for preparing nano-vaterite calcium carbonate by carbonizing carbide slag comprises the following steps:
[0057] 1) Raw material pretreatment: Dry the carbide slag at 105°C for 6 hours and then grind it for later use;
[0058] 2) Leaching: Weigh 50g of pretreated carbide slag, 60g of ammonium chloride, and 350ml of deionized water to prepare an ammonium chloride solution with a concentration of 3.0mol / L as a leaching agent. Mix and react at a stirring speed of 800r / min at room temperature for 40min, then filter to obtain a filter residue and a calcium-containing filtrate, and the filtrate is recovered and stored;
[0059] 3) Carbonization reaction: The filtrate obtained in step 2) is passed into RPB, and CO2 gas is introduced at a flow rate of 70 ml / min. The RPB rotor speed is set to 2850 r / min, and the circulation flow rate is 50 L / h. After carbonization for 60 min at room temperature, a calcium carbonate product is obtained. After filtering, washing and drying, nano-vaterite calcium carbonate is obtained. The average particle size of the powder is 70.65 nm, and the calcium utilization rate is 82.3%.
[0060] 4) The filtrate obtained in step 3) is tested and analyzed to be ammonium chloride, which can be used as a recycling leaching agent in step 2) by supplementing ammonium chloride or evaporating and concentrating.
[0061] The carbide slag selected in this embodiment has a moisture content of about 34% and a Ca(OH)2 content of about 50%.
[0062] Example 2
[0063] A method for preparing nano-vaterite calcium carbonate by carbonizing carbide slag comprises the following steps:
[0064] 1) Raw material pretreatment: Dry the carbide slag at 105°C for 6 hours and then grind it for later use;
[0065] 2) Leaching: Weigh 50g of pretreated carbide slag, 60g of ammonium chloride, and 350ml of deionized water to prepare an ammonium chloride solution with a concentration of 3.2mol / L as a leaching agent. Mix and react at a stirring speed of 800r / min at room temperature for 40min, then filter to obtain a filter residue and a calcium-containing filtrate, and the filtrate is recovered and stored;
[0066] 3) Carbonization reaction: The filtrate obtained in step 2) is passed into RPB, and CO2 gas is introduced at a flow rate of 30 ml / min. The RPB rotor speed is set to 2600 r / min, and the circulation flow rate is 100 L / h. After carbonization for 30 min at room temperature, a calcium carbonate product is obtained. After filtering, washing and drying, nano-vaterite calcium carbonate is obtained. The average particle size of the powder is 64.10 nm, and the calcium utilization rate is 83.6%.
[0067] 4) The filtrate obtained in step 3) is tested and analyzed to be ammonium chloride, which can be used as a recycling leaching agent in step 2) by supplementing ammonium chloride or evaporating and concentrating.
[0068] The carbide slag selected in this embodiment has a moisture content of about 34% and a Ca(OH)2 content of about 50%.
[0069] Example 3
[0070] A method for preparing nano-vaterite calcium carbonate by carbonizing carbide slag comprises the following steps:
[0071] 1) Raw material pretreatment: Dry the carbide slag at 105°C for 12 hours and then grind it for later use;
[0072] 2) Leaching: Weigh 100g of pretreated carbide slag, 120g of ammonium chloride, and 700ml of deionized water to prepare an ammonium chloride solution with a concentration of 4.5mol / L as a leaching agent. Mix and react at a stirring speed of 900r / min at room temperature for 60min, then filter to obtain a filter residue and a calcium-containing filtrate, and the filtrate is recovered and stored;
[0073] 3) Carbonization reaction: The filtrate obtained in step 2) is passed into RPB, and CO2 gas is introduced at a flow rate of 80 ml / min. The RPB rotor speed is set to 2850 r / min, and the circulation flow rate is 100 L / h. After carbonization for 20 min at room temperature, a calcium carbonate product is obtained. After filtering, washing and drying, nano-vaterite calcium carbonate is obtained. The average particle size of the powder is 73.51 nm, and the calcium utilization rate is 81.6%.
[0074] 4) The filtrate obtained in step 3) is tested and analyzed to be ammonium chloride, which can be used as a recycling leaching agent in step 2) by supplementing ammonium chloride or evaporating and concentrating.
[0075] The carbide slag selected in this embodiment has a moisture content of about 34% and a Ca(OH)2 content of about 50%.
[0076] Example 4
[0077] A method for preparing nano-vaterite calcium carbonate by carbonizing carbide slag comprises the following steps:
[0078] 1) Raw material pretreatment: Dry the carbide slag at 105°C for 3 hours and then grind it for later use;
[0079] 2) Leaching: Weigh 33g of pretreated carbide slag, 60g of ammonium chloride, and 350ml of deionized water to prepare an ammonium chloride solution with a concentration of 4.0mol / L as a leaching agent. Mix and react at a stirring speed of 800r / min at room temperature for 40min, then filter to obtain a filter residue and a calcium-containing filtrate, and the filtrate is recovered and stored;
[0080] 3) Carbonization reaction: The filtrate obtained in step 2) is passed into RPB, and CO2 gas is introduced at a flow rate of 60 ml / min. The RPB rotor speed is set to 2850 r / min, and the circulation flow rate is 50 L / h. After carbonization for 30 min at room temperature, a calcium carbonate product is obtained. After filtering, washing and drying, nano-vaterite calcium carbonate is obtained. The average particle size of the powder is 53.20 nm, and the calcium utilization rate is 82.5%.
[0081] 4) The filtrate obtained in step 3) is tested and analyzed to be ammonium chloride, which can be used as a recycling leaching agent in step 2) by supplementing ammonium chloride or evaporating and concentrating.
[0082] The carbide slag selected in this embodiment has a moisture content of about 34% and a Ca(OH)2 content of about 50%.
[0083] Example 5
[0084] A method for preparing nano-vaterite calcium carbonate by carbonizing carbide slag comprises the following steps:
[0085] 1) Raw material pretreatment: Dry the carbide slag at 105°C for 6 hours and then grind it for later use;
[0086] 2) Leaching: Weigh 33g of pretreated carbide slag, 60g of ammonium chloride, and 350ml of deionized water to prepare an ammonium chloride solution with a concentration of 4.0mol / L as a leaching agent. Mix and react at a stirring speed of 900r / min at room temperature for 40min, then filter to obtain a filter residue and a calcium-containing filtrate, and the filtrate is recovered and stored;
[0087] 3) Carbonization reaction: The filtrate obtained in step 2) is passed into RPB, and CO2 gas is introduced at a flow rate of 80 ml / min. The RPB rotor speed is set to 2850 r / min, and the circulation flow rate is 100 L / h. After carbonization for 15 min at room temperature, a calcium carbonate product is obtained. After filtering, washing and drying, nano-vaterite calcium carbonate is obtained. The average particle size of the powder is 55.85 nm, and the calcium utilization rate is 83.7%.
[0088] 4) The filtrate obtained in step 3) is tested and analyzed to be ammonium chloride, which can be used as a recycling leaching agent in step 2) by supplementing ammonium chloride or evaporating and concentrating.
[0089] The carbide slag selected in this embodiment has a moisture content of about 34% and a Ca(OH)2 content of about 50%.
[0090] Comparative Example 1
[0091] The same as Example 1, except that the stirring speed in the reaction and leaching stage was reduced to 700 r / min. After the same filtration, the calcium leaching rate of the product was 76%.
[0092] It can be seen from this that a decrease in stirring speed will lead to a decrease in calcium leaching rate, causing more effective calcium to be lost, thereby reducing production.
[0093] Comparative Example 2
[0094] The same as Example 1, except that the stirring time in the reaction leaching stage was reduced to 30 min, and after the same filtration, the calcium leaching rate of the obtained product was 79%.
[0095] It can be seen from this that a reduction in stirring time will lead to a decrease in the calcium leaching rate, causing more effective calcium to be lost, reducing the yield, and thus reducing production.
[0096] Comparative Example 3
[0097] The same as Example 1, except that the reaction premixing time is increased to 2 hours, after the same filtering, washing and drying treatment, the product obtained is mainly calcite-type calcium carbonate, with an average particle size of 659.2 nm and a wide particle size distribution.
[0098] It can be seen that the increase in premixing time will lead to the transformation of vaterite calcium carbonate into calcite calcium carbonate.
[0099] Comparative Example 4
[0100] The same as Example 1, except that the circulation rate of the material in the supergravity reactor is increased to 100 L / h. After the same filtering, washing and drying treatment, the product obtained is a mixture of vaterite and calcite calcium carbonate, with an average particle size of 120.0 nm.
[0101] It can be seen that under the same premixing time, an increase in circulation volume will accelerate the transformation of vaterite calcium carbonate into calcite calcium carbonate, and the particle size will increase accordingly.
[0102] Comparative Example 5
[0103] The same as Example 1, except that the flow rate of CO2 is increased to 100 mL / min. After the same premixing, filtering, washing and drying processes, the product obtained is calcite calcium carbonate.
[0104] It can be seen that under the same premixing time, an increase in the flow rate of CO2 will accelerate the transformation of vaterite calcium carbonate into calcite calcium carbonate.
[0105] Comparative Example 6
[0106] The same as Example 1, except that the premixing was carried out in a conventional stirred tank at a stirring speed of 400 r / min for 30 min, and the other conditions remained the same. The product obtained was a mixture of vaterite and calcite calcium carbonate, with an average particle size of 2.46 μm.
[0107] It can be seen that the mixing effect of the reaction materials in the traditional stirred tank is low, the particle sizes of vaterite and calcite are both large, and due to the uneven contact between CO2 gas and the liquid phase, part of the vaterite is transformed into calcite.
[0108] Comparative Example 7
[0109] The same as Example 2, except that the premixing was carried out in a conventional stirred tank at a stirring speed of 500 r / min, and the other conditions remained the same. The product obtained was vaterite with an average particle size of 1.06 μm.
[0110] It can be seen that the mixing effect of the reaction materials in the traditional stirred tank is reduced, which will lead to an increase in particle size.
[0111] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing nano-vaterite calcium carbonate from carbonized carbide slag, characterized in that: The steps include: 1) Raw material pretreatment: dry the carbide slag and grind it into powder for later use; 2) Leaching: Mix carbide slag, ammonium chloride and deionized water, stir at room temperature, and filter after reaction to obtain filter residue and calcium-containing filtrate; 3) Carbonization reaction: The calcium-containing filtrate obtained in step 2) is introduced into an external circulation supergravity reactor, and CO2 gas is introduced at the same time, and carbonization is carried out at room temperature. Nano-vaterite calcium carbonate is obtained by filtering, washing and drying.
2. according to the method for preparing nano vaterite calcium carbonate from carbonized carbide slag of claim 1, it is characterized in that: In step 1), the drying temperature is 100-110° C. and the drying time is 3-12 hours.
3. according to the method for preparing nano vaterite calcium carbonate from carbonized carbide slag of claim 1, it is characterized in that: In step 2), the weight ratio of carbide slag: ammonium chloride: deionized water is (3.3-5): (5.5-6.5): (32-37).
4. according to the method for preparing nano vaterite calcium carbonate from carbonized carbide slag of claim 1, it is characterized in that: In step 2), the concentration of the ammonium chloride solution after mixing is 3.0-4.5 mol / L.
5. according to the method for preparing nano vaterite calcium carbonate from carbonized carbide slag of claim 1, it is characterized in that: In step 2), the stirring speed is 800-900r / min.
6. according to the method for preparing nano vaterite calcium carbonate from carbonized carbide slag of claim 1, it is characterized in that: In step 2), the stirring time is 40-70 min.
7. according to the method for preparing nano vaterite calcium carbonate from carbonized carbide slag of claim 1, it is characterized in that: In step 3), the flow rate of CO2 is 30-80 ml / min.
8. according to the method for preparing nano vaterite calcium carbonate from carbonized carbide slag of claim 1, it is characterized in that: In step 3), the rotor speed in the external circulation high gravity reactor is 2000-2850 r / min.
9. according to the method for preparing nano vaterite calcium carbonate from carbonized carbide slag of claim 1, it is characterized in that: In step 3), the circulation flow rate of the reaction liquid in the external circulation supergravity reactor is 40-60 L / h.
10. The method for preparing nano-vaterite calcium carbonate from carbonized carbide slag according to claim 1, wherein: In step 3), the reaction liquid circulation time in the external circulation high gravity reactor is 20-60min; Preferably, in step 3), the washing is performed with deionized water, and the number of washing times is 3-6 times; Preferably, in step 3), the drying is oven drying, the oven drying temperature is 100-110° C., and the time is 3-12 h; Preferably, in step 3), the dried solid phase is ground to obtain nano-vaterite calcium carbonate with an average particle size of 50 to 80 nm; Preferably, in step 3), the filtrate after filtration is recovered and its concentration is adjusted to be used as a circulating leaching agent to react with carbide slag.
Citation Information
Patent Citations
Method for synthesizing ultrafine calcium carbonate by utilizing carbide slag
CN102602973A
Method for preparing nano calcium carbonate by taking carbide slag as raw material
CN103738997A
Hyper-gravity device for enhancing reaction by gas-liquid efficient premixing and application method thereof
CN107684880A
Method for preparing light calcium carbonate from carbide slag
CN110040757A
A method for preparing nanospheres of aragonite calcium carbonate from CO2-mineralized carbide slag
CN113620331B
Cited By
Method for preparing polycrystalline nano calcium carbonate from steel slag through high gravity field carbonization
CN122102189A
A method for preparing polycrystalline nanometer calcium carbonate from steel slag by carbonization in a supergravity field
CN122102189B